Cross-Strait Identity Formation Among Taiwanese Youth: Media Exposure, Political Socialization, and Civic Engagement in a Democratic Society - Yi-wei, Chu (GoAcademica Research & Publishing, 2025)
Taiwan’s evolving democratic landscape presents a unique setting for examining how youth construct their political and national identities amidst ongoing cross-Strait tensions with China. As generational shifts occur, younger Taiwanese increasingly diverge from historical narratives shaped by previous regimes, instead engaging with identity through digital media, democratic participation, and civic dialogue. This literature review explores how media exposure, political socialization, and civic engagement collectively influence the identity formation process among Taiwanese youth. Drawing from studies across political science, communication, and youth sociology, this paper synthesizes peer-reviewed literature published between 2005 and 2024. The findings reveal a growing sense of Taiwanese national identity, especially among youth with consistent exposure to local media narratives and democratic institutions. While Chinese media influence persists through digital channels, its impact is moderated by public skepticism and critical media literacy. Political socialization within families, schools, and peer groups also plays a pivotal role in shaping cross-Strait attitudes. Additionally, civic engagement practices, such as protest participation, online activism, and electoral involvement, provide meaningful pathways for youth to express and reinforce identity. However, generational divides, urban-rural disparities, and ideological fragmentation complicate a unified identity trajectory. This review highlights the need for further empirical research on identity construction mechanisms in post-authoritarian democracies. It also calls for deeper exploration into how institutional trust, transnational media, and intergenerational narratives intersect with evolving youth identities in contested geopolitical spaces.